2018
DOI: 10.14218/jcth.2018.00026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hepatitis C Treatment on Renal Function in Liver Transplant Patients

Abstract: Background and Aims: Hepatitis C Virus (HCV) is uniformly recurrent after liver transplant (LT) and recurrence is associated with an increased risk of mortality. Immunosuppressive medications increase the risk of chronic kidney disease, and the presence of chronic kidney disease presents a challenge for HCV treatment in LT recipients. The aim of this study was to assess changes in glomerular filtration rates (GFRs) of LT recipients receiving HCV treatment.Methods: This is a retrospective study of LT patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another study demonstrated a non-significant decline of eGFR from 66.8 mL/min to 64 mL/min in approximately 82% of HCV-positive patients with chronic kidney disease stage 2 or 3 after LT during treatment with sofosbuvir plus ledipasvir without ribavirin. 40 Shoreibah et al 41 found that eGFR in 65% and 35% of liver transplant recipients was stable or worsened, respectively, in HCV–positive patients who received sofosbuvir/ledipasvir without ribavirin. Patients with impaired renal function before treatment (eGFR < 60 mL/min) represent the highest proportion (48%) of those with worsened GFR 3–6 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated a non-significant decline of eGFR from 66.8 mL/min to 64 mL/min in approximately 82% of HCV-positive patients with chronic kidney disease stage 2 or 3 after LT during treatment with sofosbuvir plus ledipasvir without ribavirin. 40 Shoreibah et al 41 found that eGFR in 65% and 35% of liver transplant recipients was stable or worsened, respectively, in HCV–positive patients who received sofosbuvir/ledipasvir without ribavirin. Patients with impaired renal function before treatment (eGFR < 60 mL/min) represent the highest proportion (48%) of those with worsened GFR 3–6 months after treatment.…”
Section: Discussionmentioning
confidence: 99%